Do Not Forget the Granulocytic Compartment's Role in T cell-Mediated Antitumor Immunity - Gaipl, Udo (Cancer Immunology Research, 2024)
Antitumor immune responses are predominantly mediated by CD8+ cytotoxic T cells (CTLs). But immune-modulatory factors in the tumor microenvironment determine the effectiveness of these responses. In this issue, Wei and colleagues report a new role for CTL-derived IL3 in stimulating basophilic granulocytes to produce IL4, which, in turn, activates, reprograms, and stabilizes CTLs. These findings stress the importance of the crosstalk between the innate and adaptive immune systems to elicit efficient antitumor immunity. See related article by Wei et al., p. 822 (3).
CRIS-Team Scopus Importer:2024-07-19